2022
DOI: 10.3390/cancers14030652
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Next Generation Sequencing for Human Papillomavirus Genotyping in Cervical Liquid-Based Cytology Samples

Abstract: At present, human papillomavirus (HPV) testing is replacing morphology-based cytology as the primary tool for cervical cancer screening in several countries. However, the HPV assays approved for screening lack detection for all but one of the possibly carcinogenic HPV types and do not genotype all included HPV types. This study demonstrates the use of a targeted HPV next generation sequencing (NGS) panel to detect and genotype all 25 carcinogenic, probably carcinogenic, and possibly carcinogenic HPV types as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…On the other hand, using an NGS panel that targets all carcinogenic and probably/possibly carcinogenic HPV types, Andersen et al . demonstrated that 5 out of 93 cases (5.4%) diagnosed as atypical squamous cells of undetermined significance were positive for HPV67 in cervical-vaginal self-collected samples [ 28 ]. These estimates suggest that the rate of HPV67 infection in the general population might be higher than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, using an NGS panel that targets all carcinogenic and probably/possibly carcinogenic HPV types, Andersen et al . demonstrated that 5 out of 93 cases (5.4%) diagnosed as atypical squamous cells of undetermined significance were positive for HPV67 in cervical-vaginal self-collected samples [ 28 ]. These estimates suggest that the rate of HPV67 infection in the general population might be higher than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…The designing of the NGS HPV genotyping panel is described in detail in Andersen et al [29]. This panel includes the 25 IARC-classified carcinogenic (HPV16, 18,31,33,35,39,45,51,52,56,58,59), probably carcinogenic (HPV68), and possibly carcinogenic (HPV26, 30,34,53,66,67,69,70,73,82,85,97) HPV genotypes and the two most common low-risk HPV genotypes HPV6 and HPV11 [42].…”
Section: Ngs Hpv Genotyping Panel Design Sample Preparation and Seque...mentioning
confidence: 99%
“…In two previous studies published by our group, we validated a targeted next‐generation sequencing (NGS) panel for both HPV detection and genotyping, as well as evaluation of HPV integration status [ 28 , 29 ], which has been shown to reflect viral load [ 30 , 31 ] and prognosis [ 30 , 31 , 32 , 33 ] in CC. Integration of HPV DNA was previously considered a critical event in the process of cervical carcinogenesis [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the next-generation sequencing (NGS) can be explicitly used to improve the specificity and sensitivity of HPV detection. The NGS panel can effectively detect the presence of all HPV genotypes present in archival formalin-fixed, paraffin-embedded (FFPE), liquid-based cytology (LBC), and plasma samples [ 60 , 61 ]. Thus, the NGS technology lowers the chance of false-negative results, compared with the traditional PCR-based assays, and provides more accurate screening results for the subsequent diagnosis and treatment planning.…”
Section: Detection Of Premalignancy and Malignancy Of The Uterine Cervixmentioning
confidence: 99%